The impact of indoline derivatives on the carbohydrate metabolism of rats within a cold stress model - Lutsenko, Ruslan; Bilovol, Oleksandr; Knyazkova, Iryna; Sydorenko, Antonina; Purdenko, Tetiana; Lutsenko, Olha (Problems of Cryobiology and Cryomedicine, 2026)
This study investigated the protective effect of 2-oxoindoline-3-glyoxylic acid derivatives and its mechanisms upon cold injury in rats. The protective activity of 13 newly synthesized 2-oxoindoline-3-glyoxylic acid derivatives was evaluated at a dose of 12 mg/kg body weight administered intraperitoneally. One hour after administration, the physical endurance of male rats was assessed under cold stress conditions (water temperature +10 °C) with an additional load (10% of body weight) by measuring the duration of swimming (in seconds) until the appearance of complete fatigue (immersion). The results were compared to those of the reference substance ethylthiobenzimidazole at a dose of 50 mg/kg. The most effective results were observed after the administration of 2-hydroxy-2-(5-methyl-2-oxy-1,2-dihydroindol-3-ylidene)-N-phenylacetamide. In animals, serum glucose levels and carbohydrate metabolism indicators in hepatocytes (glycogen, glucose, pyruvate, lactate content and their ratio) were determined. It was established that administering 2-hydroxy-2-(5-methyl-2-oxy-1,2-dihydroindol-3-ylidene)-N-phenylacetamide significantly prolonged the duration of swimming in cold water, compared to both the control group and the group administered ethylthiobenzimidazole. Under hypothermic conditions, this compound prevented hypoglycaemia and positively affected carbohydrate metabolism in the liver, as evidenced by preserved glycogen, glucose and pyruvate content, and increased lactate levels. Probl Cryobiol Cryomed. 2025; 35(3):157—162